Pengaruh Suasana Toko, Kualitas Pelayanan dan Harga Terhadap Niat Beli Ulang Konsumen Di Indomaret Kota Pontianak - B31112029, SATRIO HADYAN (Jurnal Manajemen Update, 2017)
Indomaret a network mini franchises in Indonesia that provides basic needs and the needs of day - day. This study discusses there any influence of variables - variables such as store atmosphere, quality of service and price can affect the purchase intention. This research is a causal research design. The population in this study is that consumers Indomaret Pontianak. Technique Sampling used is purposivesampling.The research sample of 100 respondents, who are consumers Indomaret domiciled in Pontianak. The analytical tool used multiple linear regression by first tested the validity, reliability and classic assumption results showed that all three variables such as Atmosphere Stores, Service Quality, and Price positive and significant impact on consumer Birthday Intentions Buy Indomaret Pontianak. Service Quality most dominant influence on the intention Buy Re. Rated R2 of 0.566, meaning that 56.60% Intent to Buy Re influenced by Atmosphere Stores, Service Quality and price while the remaining 43.40% influenced by other variables not included in this study. Â  Â  Keywords: Atmosphere Stores, Service Quality, Price, Intention Buy Repeat.